Quiescence and Coral Biology: Will Warming Waters Result in a New Understanding on Coral Resiliency? - Grace, Sean P. (2018)
The objectives of this sabbatical were to examine the resilience of temperate corals (Astrangia poculata, Ellis & Solander 1787) and to address the following questions: 1. Do corals exhibit quiescence at warmer temperatures?; 2. Does Astrangia poculata exhibit quiescence across their geographic range?; 3. Does the microbial population on corals change during quiescence?; and 4. Does temperature cause a change in symbiotic state in A. poculata?
Keywords: dept.bio; faculty_collection; sabbatical_report

Encoding human serine phosphopeptides in bacteria for proteome-wide identification of phosphorylation-dependent interactions. - Barber, Karl W; Muir, Paul; Szeligowski, Richard V; Rogulina, Svetlana; Gerstein, Mark; Sampson, Jeffrey R; Isaacs, Farren J; Rinehart, Jesse (Nature biotechnology, 2018)
Post-translational phosphorylation is essential to human cellular processes, but the transient, heterogeneous nature of this modification complicates its study in native systems. We developed an approach to interrogate phosphorylation and its role in protein-protein interactions on a proteome-wide scale. We genetically encoded phosphoserine in recoded E. coli and generated a peptide-based heterologous representation of the human serine phosphoproteome. We designed a single-plasmid library encoding >100,000 human phosphopeptides and confirmed the site-specific incorporation of phosphoserine in >36,000 of these peptides. We then integrated our phosphopeptide library into an approach known as Hi-P to enable proteome-level screens for serine-phosphorylation-dependent human protein interactions. Using Hi-P, we found hundreds of known and potentially new phosphoserine-dependent interactors with 14-3-3 proteins and WW domains. These phosphosites retained important binding characteristics of the native human phosphoproteome, as determined by motif analysis and pull-downs using full-length phosphoproteins. This technology can be used to interrogate user-defined phosphoproteomes in any organism, tissue, or disease of interest.
Keywords: *Peptides/ge [Genetics]; *Protein Interaction Maps/ge [Genetics]; *Proteome/ge [Genetics]; *Serine Proteases/ge [Genetics]; 14-3-3 Proteins; 14-3-3 Proteins/ch [Chemistry]; 14-3-3 Proteins/ge [Genetics]; 14-3-3 proteins; Amino Acid Motifs; Amino Acid Motifs/ge [Genetics]; Amino acids; Article; Binding characteristics; Cellular process; DNA library; Encoding (symbols); Enzyme activity; Escherichia coli; Escherichia coli/ge [Genetics]; Gene Library; Human proteins; Humans; Motif analysis; Peptides; Peptides/ch [Chemistry]; Phosphopeptides; Phosphoproteomes; Phosphorylation; Phosphoserine; Phosphoserine/ch [Chemistry]; Plasmids; Plasmids/ge [Genetics]; Protein Interaction Maps; Protein-protein interactions; Proteome; Serine Proteases; Serine Proteases/ch [Chemistry]; Signal encoding; WW Domains; WW Domains/ge [Genetics]; WW domain; amino terminal sequence; assay; carboxy terminal sequence; cell lysate; chemistry; controlled study; dept.bio; fluorescence activated cell sorting; fusion protein; gene library; genetics; high throughput sequencing; human; immunoblotting; immunoprecipitation; in vitro study; ligand binding; mass spectrometry; nonhuman; peer-reviewed; peptide; peptide library; phosphopeptide; phosphorylation; phosphoserine; plasmid; priority journal; protein 14 3 3; protein analysis; protein degradation; protein motif; protein phosphorylation; protein protein interaction; proteome; proteomics; pull down assay; serine; serine proteinase; transcription factor FKHRL1; transfer RNA

Antibacterial Assessment of Heteroaryl, Vinyl, Benzyl, and Alkyl Tetrazole Compounds. - Dudley, Joshua; Feinn, Liana; DeFrancesco, Heather; Lindsay, Erica; Coca, Adiel; Roberts, Elizabeth Lewis (Medicinal Chemistry, 2018)
Background: In previous reports, the antibacterial properties of certain tetrazole derivatives have been described. We have previously reported the antibac...
Keywords: *Anti-Bacterial Agents/pd [Pharmacology]; *Tetrazoles/pd [Pharmacology]; 1 (1h tetrazol 5 yl)isoquinoline; 1,2 di(1h tetrazol 5 yl)ethene; 2 (1h tetrazol 5 yl)pyrazine; 4 (1h tetrazol 5 yl)pyridine; 5 (1h pyrrol 2 yl) 1h tetrazole; 5 (2 methoxybenzyl) 1h tetrazole; 5 (furan 2 yl) 1h tetrazole; 5 (naphthalen 2 ylmethyl) 1h tetrazole; 5 (pyrrol 2 yl) 1h tetrazole; 5 (thiophen 3 yl) 1h tetrazole; 5 styryl 1h tetrazole; 5-substituted 1H-tetrazoles, (3 + 2) cycloaddition; Amoxicillin; Amoxicillin/pd [Pharmacology]; Anti-Bacterial Agents; Anti-Bacterial Agents/cs [Chemical Synthesis]; Antibacterial activity; Antimicrobial activity; Article; Cerium(III) chloride heptahydrate; Escherichia coli; Escherichia coli/de [Drug Effects]; Heterocycles; Microbial Sensitivity Tests; Microwave; Molecular Structure; Pseudomonas aeruginosa; Pseudomonas aeruginosa/de [Drug Effects]; Staphylococcus aureus; Staphylococcus aureus/de [Drug Effects]; Sulfamethoxazole; Sulfamethoxazole/pd [Pharmacology]; Tetrazoles; Tetrazoles/cs [Chemical Synthesis]; Trimethoprim; Trimethoprim/pd [Pharmacology]; amoxicillin; antibacterial activity; antibiotic agent; antiinfective agent; benzilic acid derivative; carbon nuclear magnetic resonance; chemical structure; controlled study; cotrimoxazole; dept.bio; dept.che; drug effect; heating; incubation time; microbial sensitivity test; minimum inhibitory concentration; nonhuman; peer-reviewed; phenyl(1h tetrazol 5 yl)methanol; priority journal; substitution reaction; sulfamethoxazole; synthesis; tetrazole derivative; trimethoprim; unclassified drug; vinyl derivative

The gene book: Explorations in the code of life - Crawford, Sarah Adelaide (Cognella Academic Publishing, 2018)
The Gene Book: Explorations in the Code of Life is designed to introduce undergraduate college students to foundational concepts in genetics. The text provides in-depth coverage of the essential principles of genetics, from Mendel to molecular gene therapy, and reads like a story, guiding readers through each of these areas in an interesting, engaging, and enlightening way.  Milestone scientific discoveries introduce conceptual topics in each of the 10 chapters. The significance of each genetics paradigm is reinforced by the meaningful research context in which it is placed, whether the focus is single gene inheritance of disorders such as PKU and cystic fibrosis, or more complex genetic phenomena. Chromosomes, cell division, and cytogenetic disorders, including Down Syndrome and leukemia, are presented in a riveting historical context. In addition, the principles of molecular genetics are a major focus of this book. Students learn about the double helix, DNA replication, gene expression, mutation, natural selection, genomics, and the tools of molecular DNA analysis.  Approachable and effective, The Gene Book is a highly readable comprehensive text on genetics principles designed to highlight essential concepts that make up their very core. The text is well suited to undergraduate genetics courses and can also be used as a primer for more advanced undergraduate and graduate courses in medial or molecular genetics.Sarah Adelaide Crawford is professor of genetics at Southern Connecticut State University. Dr. Crawford received a Ph.D. from Columbia University College of Physicians and Surgeons, an M.S. degree in biochemistry from Princeton University, and a B.S. degree from Marymount Manhattan College. She is director of the Cancer Biology Research Laboratory and the recently opened the Autism Research Laboratory at the Southern Connecticut State University.
Keywords: dept.bio